Análise de custos de implantação e operação de sistemas de esgotamento sanitário, considerando a modicidade tarifária - Lucas Marques Pessoa (2019)
There is a consensus that the provision of wastewater services improves welfare, with health effects and economic development of the population. The Federal Law 11,445 of 2007 provides for the universalization of this service as a fundamental principle. In Brazil, it is important to make large investments in order to achieve universal access, due the existing deficit in the sector (59.7% of the population served with collection and 74.9% of the collected volume being treated in 2016, according to data from the National Sanitation Information System- SNIS). With the fiscal crisis plaguing Brazil since 2013, public resources are decreasingly to provide these necessary investments. In this way, it is believed that for the next few years the investments will come from the tariff charged for the services rendered. Therefore, it is important to estimate the investments required to provide the infrastructure and its operating costs. The universe of the study is limited to the population living in the urban centers that have a contract with a regional provider in Brazil. The costs of these infrastructures were used in the assets bank of the regional provider, and in the discretized accounting by locality for the operating costs. The per capita costs of Waste Water Treatment Plants (WWTP) technology were compared, with a sample of 348 data present in the Brazilian bibliography and from this study. It was noticeable a higher cost of implementation of WWTP that are intensive in area (lagoons), however, this same technology was the one that presented lower costs of operation of wastewater treatment. The costs of collection and treatment operation were evaluated, with data from approximately 200 municipalities with heterogeneity of characteristics (size, declivity, attendance). The operating costs, personnel and outsourced expenses accounted for 80% of the total for wastewater collection and 72% for wastewater treatment, being the most representative cost of the operation. Therefore, typical values of WWTP costs, wastewater collection system (considering pumping stations), as well as costs of collection and treatment operation, were used to estimate the attendance of 100% of the population, foreseen in the contracts of the state company under analysis. These figures served as a basis for calculating the increase in the current tariff and in the year of 2033, which works Plansab. The impact of this increase in the payment capacity of the population served, was then evaluated. It can be observed that the tariff increase in the 2033 horizon ranged from 0.96% to 2.05% among the different estimated scenarios. Per capita income growth was estimated at -1.0%, 1.2% and 2.1% for the next 15 years. It was estimated that in 62% of the time, the tariff represented less than 3% per capita income of the population (maximum value recommended by the UN). However,in 38% of the time of the estimated results, the values exceed the recommended percentage of 3%, excessively burdening the population, if the investments are all remunerated by the tariff.